Teacher Views On Text Learning Microblog Assisted Observation Reports For High Schools - Jayana, Dewi; Yunita, Dharma (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Learning by utilizing technology such as microblog in learning is believed to provide comfort and flexibility, more effective and efficient learning opportunities and experiences, improve the personal and institutional quality of students because the material studied is more interesting and not boring. This study aims to find out the expression of the teacher's views on learning the text of the observation report assisted by microblog. This study uses a descriptive qualitative method. The design of this study aims to reveal the views of Indonesian teachers regarding digital learning, the forms of activities, the methods used, and the difficulties encountered during the implementation of Indonesian language learning at school. Data collection was carried out via a Google form which was distributed to Indonesian language teachers in senior high schools. Data analysis using interactive model Miles and Huberman. The results of the study show: 1) all Indonesian teachers have the view that microblog-assisted learning is very important to implement, 2) Indonesian language learning activities especially in the text of the observation report assisted by microblog can make teachers' creativity unlimited and support a better learning process for students . The benefit of this research is that students become more active and interested in participating in learning.